Enhancing interlayer bond strength through diode laser assisted FDM process - Sabyrov, Nurbol (Nazarbayev University School of Engineering and Digital Sciences, 2020)
The most widely spread and used 3D printing technology is Fused Deposition Modeling. The main reason for such usage due to its simplicity in manufacturing and low cost. The common problem of FDM is an anisotropic property of the extruded layer. An increasing number of new filament materials and their combination in the filling process decrease bonding strength between layers. Implementation of diode (450nm) laser with 5Watt power for localized heating of the pre-deposition layer proposed to overcome this problem. By controlling the power of the laser at the moment of printing, layer interface temperature reached for critical point, where the bonding diffusion process between layers increased for maximum level. Implementation of laser-assisted heating increased the ultimate tensile strength of PLA material to 9.67% at a laser power of 2.84Watt. However, the negative impact of heating on surface roughness also observed. The excessing laser power at a certain point leads to the formation of cracks and breaks on filament layers. This thesis described a control system used for adjusting laser power. The reported method is straightforward to use for other types of heating systems. Multi-directional heating system logic also was written in this work, where 3 diode lasers installed. The controller is capable of controlling many lasers at one time. In the case of printing objects with different filaments, it is also could be rewritten into controlling laser power deepened on filament type. The effect of the implementation of laser is analyzed from the energy and economic point of view. Even though energy consumption increases by 48% for energy cost, it is negligible. Regarding the financial aspect of implementation, the fixed price will rise by 53%, whereas the cost of electricity will be insignificant. Generally, the optimization of this method could bring more valuable benefits for the mechanical property of the FDM fabricated product.
Keywords: FDM; laser; interlayer diffusion; anisotropy